The sociological study of nurse-physician professional relationship in Iran - Maryam Mehrabi; Ali Madanipour; Shirin Ahmadnia (Iranian Journal of Nursing and Midwifery Research, 2016)
Background: During recent decades, various factors have modified the nurse–physician professional relationship pattern in hospital settings. The present study investigates the typology and dynamics of this relationship as well as the effects of social structures and the actors' agency by considering the gender variable in two professional groups of nurse and physician. Materials and Methods: A survey was conducted in 2009 using a quota sampling method of 100 female nurses and male physicians in four hospitals in Tehran. Results: The study revealed three distinct patterns of nurse–physician professional relationship including “dependence–independence,” “nondominance–dominance,” and “cooperation–participation.” Occupational socialization, gender stereotypes, organization support, and actors' agency were discovered as the most effective factors. Conclusions: Observing caution in generalizing the results, the predominant relationship pattern was derived from the persistence of gender stereotypes in the occupational context. Although there is a paradigm shift in the relational and embodied structures, balancing power resources are being formed by younger nurses who require more organizational support to improve the professional fulfilment and authority.